The “White Ocean” Hypothesis: A Late Pleistocene Southern Ocean Governed by Coccolithophores and Driven by Phosphorus - Flores, Jose A.; Filippelli, Gabriel M.; Sierro, Francisco J.; Latimer, Jennifer C. (Frontiers in Microbiology, 2012)
Paleoproductivity is a critical component in past ocean biogeochemistry, but accurate reconstructions of productivity are often hindered by limited integration of proxies. Here, we integrate geochemical (phosphorus) and micropaleontological proxies at millennial timescales, revealing that the coccolithophore record in the Subantarctic zone of the South Atlantic Ocean is driven largely by variations in marine phosphorus availability. A quantitative micropaleontological and geochemical analysis carried out in sediments retrieved from ODP Site 1089 (Subantarctic Zone) reveals that most of the export productivity in this region over the last 0.5 my was due to coccolithophores. Glacial periods were generally intervals of high productivity, with productivity reaching a peak at terminations. Particularly high productivity was observed at Termination V and Termination IV, events that are characterized by high abundance of coccolithophores and maxima in the phosphorus/titanium and strontium/titanium records. We link the increase in productivity both to regional oceanographic phenomena, i.e., the northward displacement of the upwelling cell of the Antarctic divergence when the ice-sheet expanded, and to the increase in the inventory of phosphorus in the ocean due to enhanced transfer of this nutrient from continental margins during glacial lowstands in sea level. The Mid-Brunhes interval stands out from the rest of the record, being dominated by the small and highly-calcified species Gephyrocapsa caribbeanica that provides most of the carbonate in these sediments. This likely represents higher availability of phosphorus in the surface ocean, especially in mesotrophic and oligotrophic zones. Under these condition, some coccolithophore species developed an r-strategy (opportunistic species; growth rate maximized) resulting in the “bloom” of G. caribbeanica. These seasonal blooms of may have induced“white tides” similar to those observed today in Emiliania huxleyi.